NprR-NprX Quorum-Sensing System Regulates the Algicidal Activity of Bacillus sp. Strain S51107 against Bloom-Forming Cyanobacterium Microcystis aeruginosa - Lishuang Wu; Xingliang Guo; Xianglong Liu; Hong Yang (Frontiers in Microbiology, 2017)
Harmful cyanobacterial blooms have severely impaired freshwater quality and threatened human health worldwide. Here, a Gram-positive bacterium, Bacillus sp. strain S51107, which exhibits strong algicidal activity against Microcystis aeruginosa, was isolated from Lake Taihu. We found that the algicidal activity of strain S51107 was regulated primarily by NprR-NprX quorum sensing (QS), in which the mature form of the signaling peptide NprX was identified as the SKPDIVG heptapeptide. Disruption of the nprR-nprX cassette markedly decreased the algicidal activity, and complemented strains showed significantly recovered algicidal activity. Strain S51107 produced low-molecular-weight algicidal compounds [indole-3-carboxaldehyde and cyclo(Pro-Phe)] and high-molecular-weight algicidal substance(s) (>3 kDa). Moreover, the production of high-molecular-weight algicidal substance(s) was regulated by NprR-NprX QS, but the production of low-molecular-weight algicidal compounds was not. High-molecular-weight algicidal substance(s) played a more important role than low-molecular-weight algicidal compounds in the algicidal activity of strain S51107. The results of this study could increase our knowledge about algicidal characteristics of a potential algicidal bacterium, Bacillus sp. strain S51107, and provide the first evidence that the algicidal activity of Gram-positive algicidal bacteria is regulated by QS, which will greatly enhance our understanding of the interactions between algae and indigenous algicidal bacteria, thereby providing aid in the design and optimization of strategies to control harmful algae blooms.